Challenges in Hypermature Senile Cataract with Intracapsular Cataract Extraction for Wide Zonular Dehiscence: A Case Study - Imelda, Eva; Jannah, Raudhatul; Jannah, Siti Rain; Adev, Sarra Mutiara; Toshniwal, Navneet Shamsundar (Heca Sentra Analitika, 2023)
A cataract is a condition characterized by clouding of the eye's lens. Senile cataracts progress through four stages: incipient, immature, mature, and hypermature. These stages are determined by the degree of lens cloudiness and the extent of lens mass involvement. In the hypermature stage, the entire lens capsule becomes wrinkled, and its contents become either solid and wrinkled or soft and liquid. An 83-year-old female patient presented to the Department of Ophthalmology at RSUD dr. Zainoel Abidin Banda Aceh with a gradual decrease in vision over the past four years. Ophthalmological examination using a slit lamp revealed cloudiness throughout the lens mass, a brownish-white lens color, wrinkling of the anterior capsule, and visible zonular dehiscence at approximately 90 degrees. The patient's left eye pressure measured 23 mmHg. A surgical plan for Intracapsular Cataract Extraction (ICCE) was made. Despite the surgery, the patient's visual function remained poor. Consequently, a second surgery for IOL insertion was scheduled six weeks after the initial procedure. The patient's visual function is anticipated to improve following the second IOL insertion surgery.